A new Reed Frog (Hyperoliidae: Hyperolius) from coastal northeastern Mozambique - Conradie, Werner; Verburgt, Luke; Portik, Daniel M.; Ohler, Annemarie; Bwong, Beryl A.; Lawson, Lucinda P. (Zootaxa, 2018)
A new species of African reed frog (genus Hyperolius Rapp, 1842) is described from the Coastal Forests of the Eastern Africa Biodiversity Hotspot in northeastern Mozambique. It is currently only known from less than ten localities associated with the Mozambican coastal pans system, but may also occur in the southeastern corner of Tanzania. Phylogenetic reconstructions using the mitochondrial 16S marker revealed that it is the sister taxon of Hyperolius mitchelli (>5.6% 16S mtDNA sequence divergence) and forms part of a larger H. mitchelli complex with H. mitchelli and H. rubrovermiculatus. The new species is distinguished from other closely related Hyperolius species by genetic divergence, morphology, vocalisation, and dorsal colouration.